The Clinical Characteristics of Epileptic Pregnant Women - Erdemoğlu, Mahmut; Kuyumcuoğlu, Umur; Güzel, Ali İrfan (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: We aimed to report the clinical characteristics 16 pregnant epileptic women applied to our clinic. STUDY DESIGN: The data were collected from the hospital records and patient files retrospectively. RESULTS: Our study indicates that the rate of complications of pregnancy in mothers with active epilepsy is low and similar to that of the general population with epilepsy. There were no maternal or perinatal deaths. CONCLUSION: It is concluded that epileptic women may expect good maternal and fetal outcome with qualified prenatal medical and obstetric care.